2022
DOI: 10.3390/bios12090726
|View full text |Cite
|
Sign up to set email alerts
|

A Salmonella Microfluidic Chip Combining Non-Contact Eddy Heater and 3D Fan-Shaped Mixer with Recombinase Aided Amplification

Abstract: Foodborne pathogenic bacteria have become a worldwide threat to human health, and rapid and sensitive bacterial detection methods are urgently needed. In this study, a facile microfluidic chip was developed and combined with recombinase-aided amplification (RAA) for rapid and sensitive detection of Salmonella typhimurium using a non-contact eddy heater for dynamic lysis of bacterial cells and a 3D-printed fan-shaped active mixer for continuous-flow mixing. First, the bacterial sample was injected into the chip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…This suggests that the cost of real-time RT-RAA amplification can be further reduced by reducing the reaction volume. In addition, real-time RT-RAA amplification can also be combined with microfluidic chip technology for multipathogen detection [ 25 ]. In addition, several studies have shown that the combination of RAA technology and the CRISPR system can achieve ultrahigh sensitivity and specific detection of single DNA or RNA molecules [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the cost of real-time RT-RAA amplification can be further reduced by reducing the reaction volume. In addition, real-time RT-RAA amplification can also be combined with microfluidic chip technology for multipathogen detection [ 25 ]. In addition, several studies have shown that the combination of RAA technology and the CRISPR system can achieve ultrahigh sensitivity and specific detection of single DNA or RNA molecules [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to statistics, there are 2,643 cases in Asia, and up to 9,200,000 total cases of food borne diseases occur annually in the USA and in Europe . These adverse effects of food globalization and immediate health safety threats drive the advancement of the quality of the sensors, which require rapid detection for the presence of preservatives, pathogens, allergens, , insecticides, , and heavy metals in food. One method for food testing is performed manually, such as observation, smell, and taste, but these assessments are prone to human error.…”
Section: D Printed Sensors For Food Safety Purposesmentioning
confidence: 99%
“…Regarding the RPA/RAA assay, the manual operations and cumbersome peripheral equipment required during nucleic acid extraction, amplification, and detection present challenges that limit the widespread field-testing applications of this technology. Integrating RPA/RAA with other systems, such as microfluidics ( Qi et al, 2023 , Wu et al, 2022 ), could potentially address these challenges and result in more rapid, stable, and easy-to-operate on-site detection tools that require minimal labor, time, and energy consumption. Furthermore, the present expenses associated with utilizing RPA technology are high, rendering it inaccessible to some due to the limited availability of RPA kits sold by only two companies ( Tan et al, 2022 ).…”
Section: Remaining Challenges and Possible Opportunitiesmentioning
confidence: 99%
“…Simplification is crucial to reduce the time required for sample pre-treatment/preparation, amplification, and readout detection. Integration with other essential technologies, such as biosensors, CRISPR/Cas-based technology, microfluidic chips, and nanotechnology, may provide ultrafast NAA with higher sensitivity, rapidity, and specificity ( Gao et al, 2022 , Huang et al, 2023b , Kabiraz et al, 2023a , Qi et al, 2023 , Saravanan et al, 2021 , Wu et al, 2022 , Xu et al, 2021 , Yin et al, 2022 , Yin et al, 2019 ). Finally, miniaturizing user-friendly, inexpensive, intelligent, and portable NAA tools may facilitate the widespread use of this technology for routine monitoring of microbial hazards in foods worldwide.…”
Section: Remaining Challenges and Possible Opportunitiesmentioning
confidence: 99%